EFL students’ experiences with blog-integrated writing instruction - Kızıl, Aysel Şahin; Arslan, Recep Şahin (My University, 2012)
With the advent of the Internet, various tools (e.g. wikis, discussion forums, blogs) have been redefining the way we teach writing. Among internet based applications, blogging especially attracts attention with its user-friendly and open-to-anyone nature, hyperlinked post structure and options for comment and reply that foster interaction. As it is directly related to writing, blogging has currently been regarded as a natural tool for writing instruction. [1]. Describing a blog-integrated writing course, this paper presents the results of a study on students’ perceptions towards blog use as a means of writing. 27 intermediate level university students were instructed according to the principles of process approach and they were required to carry on stages of writing process (drafting, revising etc ...) through blog software. The study lasted for 16 weeks and at the end of the course, the students were given a Post Instruction Perception Questionnaire divided into four categories: student perceptions towards effect of a) blog use on overall writing performance; b) blog use on the components of writing; c) blog use on the feedback and revision; d) effect of blogging on interest, motivation and technology use.The results showed that the students had a positive perception of blog use in their writing course and they believed that carrying on the writing activities through blog software especially contributed to the improvement of the content and organization of their writings.
Bildiri - Yayımlanmış
Keywords: Blog; English as a foreign language; Writing instruction